(untitled) - OLAYLNKA, AKINYOMI (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Organic amendments which were mixed with sieved (2mm) air-dry sol/ at the rete o/ 3% Included poultry manure and 4:11 and 1:1 mixtures of poultry manure and corn L,) stew or sawdust obtained from Canarium schweinfurthii (Engl.) respectively, The treatment, Including control, were Incubated for 8 weeks at 3000 In the laboratory, Amounts of C evolved as C02 which 18 an index of C mineralization were determined weekly. The Incorporation of organic amendments Increased the amount of C mineralized from the treatments, Two peeks of C evolution were observed at the ends of the 1st and 3rd weeks, The first peek was probably due to the easily oxidizable C while the second peak was the result of the activity of microorganisms adaptable to the more recalcitrant C fractions. Carbon evolution from poultry manure-straw/sawdust treatments were significantly higher (32-85%) than in the presence of poultry manure alone. Both the mean rates and cumulative amounts of C mineralized generally increased with increasing contents of straw and sawdust. However, the type of plant residue mixed with poultry manure did not significantly influence the amounts of C mineralized at the comparative rates of addition. The % of added C mineralized decreased with increasing contents of straw and sawdust. Correlation studies showed that the C/N ratios of the amendments had significant negative effect (r = 0.91) on the degree of C mineralization in soil. Carbon/nitrogen ratio had no significant effect on the cumulative amounts of C mineralized. These results indicate the importance of C/N ratio to the rate of decomposition of organic amendments in soil.